A preliminary assessment of freshwater snails in selected barangays in aAlang- Alang, Leyte - Carlobos, Peter John C. (2017)
The Leyte and Samar islands have no updated inventory in the biodistribution of its freshwater gastropod species. Moreover, no studies related to the taxonomy of all freshwater snails have been conducted in Alang- Alang, Leyte Thus, this study is aimed to survey the freshwater snails present in the municipality. Freshwater snails were collected in accessible collecting stations within selected barangays through intensive snail search and random ring sampling in March 2017.